Class 9 Maths NCERT Solutions of Chapter 2-Polynomial - Future Study Point

# Class 9  NCERT Solutions of  Chapter 2-Polynomial

The NCERT solutions of class 9 maths chapter 2- Polynomial is a basic chapter of algebra. The NCERT solutions of chapter 2-Polynomial will help you in understanding the questions based on the different structures of polynomials. The NCERT solutions of chapter 2-Polynomial provide the use of all algebraic identities which are used in higher classes and also in other branches of mathematics. All the NCERT solutions of chapter 2-Polynomial are solved by an expert teacher of maths as per the CBSE norms.

Polynomial is an algebraic expression in which the degree of the variable is a whole number as an example x, x +1,x²+1, etc but constants like 1,2,3 3/2, etc are also supposed as a polynomial because we can write them x0,2x0,3x0,3x0/2etc.In terms of the number of terms, polynomials are classified as monomial(single), binomial(two terms), trinomial(three terms), etc. In terms of degree, the polynomials are classified as linear polynomials (degree 1), quadratic polynomials (degree 2), cubic polynomials (degree 3), etc.

Click for online shopping

Future Study Point.Deal: Cloths, Laptops, Computers, Mobiles, Shoes etc

Chapter 2 Polynomial of Class 9 contains 5 exercises

Exercise 2.1

Exercise 2.2

Exercise 2.3

Exercise 2.4

Exercise 2.5

NCERT Solutions of all chapters of Maths for Class 10 from Chapters 1 to 15

NCERT Solutions of Class 9 Maths : from chapter 1 to 15

You can also see the video NCERT Solutions for Class 10 Maths Chapter 2 -Polinomial updated for 2023-24 CBSE Board Exams,these NCERT solutions are referred to Chapter- 2 Current maths NCERT text book.

## Class 9 maths NCERT Solutions of the chapter 2-Polynomial

Shopify e-books of Science & Maths of all classes

### Exercise 2.1

Q1. Which of the following expressions are polynomials in one variable and which are not? State reasons for your answer.

(i) 4x² –3x + 7

(ii)  y² + √2

(iii) 3√t  + t√2

Ans. (i) 4x² –3x + 7

Hint: Polynomial is the algebraic expression in which the power of the variable is a whole number

The given expression is a polynomial in one variable x since each power of x (2,1,0) is a whole number

(ii) y² + √2

The given expression is polynomial in one variable y since each  power of y (2,0) is a whole number

(iii) 3√t  + t√2

The given expression is not a polynomial since the power of variable t is (1/2, 1)  in which 1/2 is not a whole number

The given expression is not a polynomial since the power of variable y is (1, –1) in which –1 is not a whole number.

The given expression is a polynomial in three variables x,y, and t since each exponent of the variable is 10, 3, and 50 in which all are whole numbers.

Q2.Write the coefficient of x² in each of the following.

(i) 2 + x² + x

(ii) 2 – x² + x³

Ans.

(i) 2 + x² + x

In the given expression the term containing x² has the coefficient 1

(ii) 2 – x² + x³

In the given expression the term containing  x² has the coefficient –1

In the given expression the term containing x² has the coefficient π/2.

In the given expression there is no any term x², so the coefficient of x² is 0.

Q3. Give one example each of a binomial of degree 35, and a monomial of degree 100.

Ans. Binomial of degree 35 is following

Monomial of degree 100 is following

Q4. Write the degree of the following polynomial

(i) 5x³ + 4x² + 7x

(ii) 4 – y²

(iii)5t –√7

(iv) 3

Ans.

(i) 5x³ + 4x² + 7x

The highest exponent of the variable x is 3, so the degree of the given polynomial is 3

(ii) 4 – y²

The highest exponent of the variable y in the expression is 2, so the degree of the polynomial is 2

(iii)5t –√7

The highest exponent of the variable t in the expression is 1, so the degree of the polynomial is 1

(iv) 3

There is no variable in the given term, so the degree of the polynomial is 0

Q5. Classify the following as linear, quadratic, and cubic polynomial.

(i) x² + x

(ii) x – x³

(iii) y + y² + 4

(iv) 1 + x

(v) 3t

(vi) r²

(vii) 7x³

Ans.

(i) x² + x

The given polynomial is of the degree 2, so it is a quadratic polynomial

(ii) x – x³

The given polynomial is of the degree 3, so it is a cubic polynomial

(iii) y + y² + 4

The given polynomial is of the degree 2, so the given polynomial is a quadratic polynomial

(iv) 1 + x

The given polynomial is of the degree 1, so the given polynomial is a linear polynomial

(v) 3t

The given polynomial is of the degree 1, so the given polynomial is a linear polynomial

(vi) r²

The given polynomial is of the degree 2, so the given polynomial is a quadratic polynomial

(vii) 7x³

The given polynomial is of the degree 3, so the given polynomial is a cubic polynomial

## Class 9 Maths NCERT Solutions of Chapter 2-Polynomial

### Exercise 2.2

Q1. Find the value of polynomial 5x –4x² +3 at

(i) x = 0 (ii)x = –1  (iii) x = 2

Ans. Let the given polynomial is expressed as p(x)

(i) x = 0

p(x) = 5x –4x² +3

p(0) = 5× 0 –4 × 0 + 3 = 3

(ii)x = –1

p(x) = 5x –4x² +3

p(–1) = 5 ×–1 – 4 (–1) ² + 3 = –5 –4 + 3 = –9 + 3 = –6

(iii) x = 2

p(x) = 5x –4x² +3

p(2) = 5 × 2 – 4 ×2² + 3 = 10 – 16 + 3 = –3

Q2.Find p(0), p(1) and p(2) for each of the following polynomials

(i) p(y) = y² –y + 1

(ii) p(t) = 2 +t  +2t² – t³

(iii) p(x) = x³

(iv) p(x) = (x +1)(x – 1)

Ans.

(i) p(y) = y² –y + 1

p(0) = 0 – 0 +1 = 1

p(1)  = 1² –1 + 1 = 1

p(2) = 2² –2 + 1 = 3

(ii) p(t) = 2 +t  +2t² – t³

p(0) = 2 +0 +2×0² – 0³= 2

p(1) = 2 +1  +2×1² – 1³ = 3 +2 – 1 = 4

p(2)=2 +2 +2×2² – 2³ = 4 + 8 – 8 = 4

(iii) p(x) = x³

p(0) = 0³ = 0

p(1) = 1³ = 1

p(2) = 2³ = 8

(iv) p(x) = (x +1)(x – 1)

p(0) = (0+1)(0 – 1) = –1

p(1) = (1 +1)(1 – 1) = 0

p(2) = (2 +1)(2 – 1) = 3

Q3. Verify whether the following are zeroes of the polynomial , indicated against them.

Ans.

Since the value of the polynomial at x = – 1/3 is zero, so x = – 1/3 is the zero of the given polynomial

The value of the polynomial is not zero at the value ,x = 4/5, so x = 4/5 is not the zero of the given polynomial

p(1) = 1² – 1 = 0

The value of the polynomial at x = 1, is zero, so x = 1 is the zero of the given polynomial.

The value of the polynomial at x = –1/2, is not zero, so x = –1/2  is not the zero of the given polynomial.

p(0) = 0

The value of the polynomial at x = 0, is  zero, so x = 0  is  the zero of the given polynomial

The value of the polynomial at x = –m/l  is  zero, so x = –m/l  is  the zero of the given polynomial

The value of the polynomial at x = –1/l√3 is  zero, so x = –1/√3  is  the zero of the given polynomial

The value of the polynomial at x = 2/√3 is  not zero, so x = 2/√3  is  not the zero of the given polynomial

The value of the polynomial at x = 1/2 is  not zero, so x = 1/2  is  not the zero of the given polynomial

Q4. Find the zero of the polynomial in each of the given cases.

(i) p(x) =  x +5

(ii) p(x) =  x – 5

(iii) p(x) = 2 x  + 5

(iv) p(x) =  3x – 2

(v) p(x) = 3x

(vi) p(x) =  ax, a ≠ 0

(vii) p(x)  = cx + d, c ≠ 0 where c and d are real numbers

Ans.

(i) p(x) =  x +5

x +5 = 0

x = – 5

Hence the zero of the given polynomial is x =– 5

(ii) p(x) =  x – 5

x – 5 = 0

x = 5

Hence the zero of the given polynomial is x = 5

(iii) p(x) = 2 x  + 5

2 x  + 5 = 0

Hence the zero of the given polynomial is – 5/2

(iv) p(x) =  3x – 2

3x – 2 = 0

Hence the zero of the given polynomial is  2/3

(v) p(x) = 3x

3x = 0

x = 0

Hence the zero of the given polynomial is  0

(vi) p(x) =  ax, a ≠ 0

ax = 0

x = 0

Hence the zero of the given polynomial is  0

vii) p(x)  = cx + d

cx + d = 0

Hence   zero of the given polynomial is  – d/c

## Class 9 Maths NCERT Solutions of Chapter 2-Polynomial

EXERCISE-2.3

Q1.Find the remainder when is divided by

(i) x

(iii) x

(iv) x+π

(v) 5+2x

Ans.

(i)   We have to divide  the polynomial  by  the polynomial  x + 1

Let’s find the zero of the   x  = 0

x  = – 1

Putting the value of x = – 1, in

= – 1 + 3 – 3 + 1 = 0

(ii) Dividing the polynomial      by     , we can get the reminder in the following way

Putting the value        in

(iii) Dividing the polynomial     by x, we can get the reminder by the following way

Putting x = 0  the zero of the polynomial x, in the given polynomial

0 + 0 + 0 +1 = 1

(iv)   Dividing the polynomial     by x + π, we can get the reminder by the following way

x + π = 0

x = – π , is the zero of the polynomial x + π

Putting the value x = – π, in the given polynomial

The reminder is

(v) Dividing the polynomial     by 5 + 2x, we can get the reminder by the following way

5+2x = 0

, is the zero of the polynomial  5+2x

Putting the value of         in the polynomial , we get the reminder

Q2.Find the remainder when   is divided by .

The zero the polynomial x – a, is

x – a = 0

x = a

Putting this value in

a³ –  a × a² + 6 × a – a

= a³ – a³ +6a – a = 5a

Therefore the required reminder is 5a

Q3.Check whether  is a factor of .

The zero of the polynomial  7 + 3x is as follows

7 + 3x = 0

Putting this value of x in , we shall get the required reminder

## Class 9 Maths NCERT Solutions of Chapter 2-Polynomial

### EXERCISE-2.4

Q1.Determine which of the following polynomials has a factor.

(i)

(ii)

(iii)

(iv)

Ans.

(i)

The zero of the polynomial  x + 1 is as follows

x + 1 = 0

x = – 1

Putting this value of x = – 1, in the given polynomial

(–1)³ + 1² + 1 + 1

– 1 + 1 + 1 + 1 = 2

Since value of the polynomial at x = – 1, is not zero so  (x +1) is not the factor of the given polynomial

(ii)

The zero of the polynomial (x +1)  is x + 1 = 0 ⇒ x = – 1

Putting x = – 1, in the given polynomial

= 1 – 1 + 1 – 1 + 1 = 1

Since value of the given polynomial at x = 1, is not zero,therefore (x +1) is not the factor of the given polynomial

(iii)

The zero of the polynomial (x +1)  is x + 1 = 0 ⇒ x = – 1

Putting x = – 1, in the given polynomial

= 1 – 3 + 3 –1 +1 = 1

Since value of the given polynomial at x = 1, is not zero,therefore (x +1) is not the factor of the given polynomial

(iv)

The zero of the polynomial (x +1)  is x + 1 = 0 ⇒ x = – 1

Putting x = – 1, in the given polynomial

The value of the polynomial  at x = – 1  is not zero, so (x + 1) is not the factor of the given polynomial

Q2. Use the Factor Theorem to determine whether g (x) is a factor of p (x) in each of the following cases
(i) p (x)= 2x3 + x2 – 2x – 1, g (x) = x + 1
(ii) p(x)= x3 + 3x2 + 3x + 1, g (x) = x + 2
(iii) p (x) = x3 – 4x2 + x + 6, g (x) = x – 3

Ans. (i) p (x)= 2x3 + x2 – 2x – 1, g (x) = x + 1

x + 1 = 0

x = – 1

Putting the value of x = – 1 in the given polynomial

p(x) = 2x3 + x2 – 2x – 1

= 2× – 1 + 1 + 2 – 1

p(–1) =  – 2 + 3 – 1 = 0

Since  value of  p(–1) is zero ,therefore g(x) is the factor of the given polynomial

(ii) p(x)= x3 + 3x2 + 3x + 1, g (x) = x + 2

x + 2 = 0

x = – 2

p(x)= x3 + 3x2 + 3x + 1

p(– 2) = (– 2)3  + 3(–2)² + 3 (– 2) +1 = -8 +12 -6 +1 = -1

Since the value of p(– 2) is not zero, therefore the given polynomial is not the factor of  (x + 2)

(iii) p (x) = x3 – 4x2 + x + 6, g (x) = x – 3

x – 3 = 0

x = 3

Putting the value of x in the given polynomial

p(3) = 3³ –4× 3² + 3 + 6

= 27– 36 + 9

= 0

Since the value of   p(3) is  zero,  so  g(x)  is the factor of   p(x)

Q3.Find the value of k, if x – 1 is a factor of p (x) in each of the following cases
(i) p (x) = x2 + x + k
(ii) p (x) = 2x2 + kx + √2
(iii) p (x) = kx2 – √2 x + 1
(iv) p (x) = kx2 – 3x + k
Ans.
For (x – 1) to be a factor of p(x), p(1) should be equal to 0.

(i) Here, p(x) = x2 + x + k
Since, p(1) = (1)2 +1 + k
⇒ p(1) = k + 2 = 0
⇒ k = -2.

(ii) Here, p (x) = 2x2 + kx + √2
Since, p(1) = 2(1)2 + k(1) + √2
= 2 + k + √2 =0
k = -2 – √2 = -(2 + √2)

(iii) Here, p (x) = kx2 – √2 x + 1
Since, p(1) = k(1)2 – (1) + 1
= k – √2 + 1 = 0
⇒ k = √2 -1

(iv) Here, p(x) = kx2 – 3x + k
p(1) = k(1)2 – 3(1) + k
= k – 3 + k
= 2k – 3 = 0
⇒ k =

Q4. Factorise
(i) 12x2 – 7x +1
(ii) 2x2 + 7x + 3
(iii) 6x2 + 5x – 6
(iv) 3x2 – x – 4
Ans.
(i) We have,
12x2 – 7x + 1 = 12x2 – 4x- 3x + 1
= 4x (3x – 1 ) -1 (3x – 1)
= (3x -1) (4x -1)
Thus, 12x2 -7x + 3 = (2x – 1) (x + 3)

(ii) We have, 2x2 + 7x + 3 = 2x2 + x + 6x + 3
= x(2x + 1) + 3(2x + 1)
= (2x + 1)(x + 3)
Thus, 2×2 + 7x + 3 = (2x + 1)(x + 3)

(iii) We have, 6x2 + 5x – 6 = 6x2 + 9x – 4x – 6
= 3x(2x + 3) – 2(2x + 3)
= (2x + 3)(3x – 2)
Thus, 6x2 + 5x – 6 = (2x + 3)(3x – 2)

(iv) We have, 3x2 – x – 4 = 3x2 – 4x + 3x – 4
= x(3x – 4) + 1(3x – 4) = (3x – 4)(x + 1)
Thus, 3x2 – x – 4 = (3x – 4)(x + 1)

Q5. Factorise
(i) x3 – 2x2 – x + 2
(ii) x3 – 3x2 – 9x – 5
(iii) x3 + 13x2 + 32x + 20
(iv) 2y3 + y2 – 2y – 1
Ans.
(i) We have, x3 – 2x2 – x + 2
Rearranging the terms, we have x3 – x – 2x2 + 2
= x(x2 – 1) – 2(x2 -1) = (x2 – 1)(x – 2)
= [(x)2 – (1)2](x – 2)
= (x – 1)(x + 1)(x – 2)
[∵ (a2 – b2) = (a + b)(a-b)]
Therefore , x3 – 2x2 – x + 2 = (x – 1)(x + 1)(x – 2)

(ii) We have, x3 – 3x2 – 9x – 5
= x3 + x2 – 4x2 – 4x – 5x – 5 ,
= x2 (x + 1) – 4x(x + 1) – 5(x + 1)
= (x + 1)(x2 – 4x – 5)
= (x + 1)(x2 – 5x + x – 5)
= (x + 1)[x(x – 5) + 1(x – 5)]
= (x + 1)(x – 5)(x + 1)
Therefore, x3 – 3x2 – 9x – 5 = (x + 1)(x – 5)(x +1)

(iii) We have, x3 + 13x2 + 32x + 20
= x3 + x2 + 12x2 + 12x + 20x + 20
= x2(x + 1) + 12x(x +1) + 20(x + 1)
= (x + 1)(x2 + 12x + 20)
= (x + 1)(x2 + 2x + 10x + 20)
= (x + 1)[x(x + 2) + 10(x + 2)]
= (x + 1)(x + 2)(x + 10)
Therefore, x3 + 13x2 + 32x + 20
= (x + 1)(x + 2)(x + 10)

(iv) We have, 2y3 + y2 – 2y – 1
= 2y3 – 2y2 + 3y2 – 3y + y – 1
= 2y2(y – 1) + 3y(y – 1) + 1(y – 1)
= (y – 1)(2y2 + 3y + 1)
= (y – 1)(2y2 + 2y + y + 1)
= (y – 1)[2y(y + 1) + 1(y + 1)]
= (y – 1)(y + 1)(2y + 1)
Therefore, 2y3 + y2 – 2y – 1
= (y – 1)(y + 1)(2y +1)

## Class 9 Maths NCERT Solutions of Chapter 2-Polynomial

### Exercise 2.5

Q1.Use suitable identities to find the following products

(i)

(ii)

(iii)

(iv)

Ans.

(i)  (x + 4)( x+ 10)

Q2.Evaluate the following products without multiplying directly:

(i)103×107

(ii)95×96

(iii)104× 96

Ans.

(i)103×107

Modifying the given expression in form of (x + a)(x +b) as following

(103)×(107) = (100 +3)(100 +7)

(100 +3)(100 +7) = 100² +(3 +7)100 + 3×7 = 10000 +1000 + 21 = 110021

(ii) 95×96

95×96  = (100 – 5)(100  –  4)

(100 – 5)(100  –  4) = 100² +( – 5 –  4)100 +( – 4)( – 5)

10000 – 900 + 20 = 9120

(iii) 104× 96

(100 +4)(100 – 4)

(100 +4)(100 – 4) = 100² – 4² = 10000 – 16 = 9984

Q3.Factorize the following using appropriate identities

(i)

(ii)

(iii)

Ans.

(i)

Using the following identity

(ii)

(iii)

Q4.Expand each of the following, using a suitable identity

(i)

(ii)

(iii)

(iv)

(v)

(iv)

Ans.

(i)

(ii)

(iii)

(iv)

(v)

(iv)

Q5.Factorise:

(i)

(ii)

Ans.

(i)

Since the terms –24yz and –16xz, both are having negative sign, so the term z which is common between them must be negative

(ii)

Q6.Write the following cubes in expanded form

Ans.

Applying the following identity

=

Applying the following identity

Using the following identity

Q7.Evaluate the following using suitable identities

(i)99³      (ii)102³    (iii) 998³

Ans.

(i)99³

Modifying 99 into (100– 1) and using the following identity

(x +y)³ = x³ + 3x²y + 3y²x + y³

= 1000000 – 30000 + 300 – 1

= 970299

(ii)102³

Modifying 102 into ( 100 +2) and using the following identity

(x +y)³ = x³ + 3x²y + 3y²x + y³

(100 +2)³ = 100³  + 3× 100² ×2 + 3×2²× 100 + 2³

= 1000000 + 60000 +1200 +8

=1061208

(iii) 998³

Modifying the number 998 into (1000 – 2) and using the following identity

(x +y)³ = x³ + 3x²y + 3y²x + y³

(1000 –2)³ = 1000³  – 3× 1000² ×2 + 3×2²× 1000 – 2³

1000000000 –6000000 +12000 – 8

=994011992

Q8.Factorise each of the following

(1) 8a³ + b³ +12a²b + 6ab²

(ii) 8a³ – b³ – 12a²b + 6ab²

(iii) 27 – 125a³ – 135a + 225a²

(iv) 64a³ – 27b³ – 144a²b + 108b²a

Ans.

(1) 8a³ + b³ +12a²b + 6ab²

Using the following identity

(x + y)³ = x³ + y³ +3x²y + 3y²x

Modifying the given expression as following

(2a)³ + b³ +3×(2a)²×b + 3×b²×2a

= (2a + b)³

(ii) 8a³ – b³ – 12a²b + 6ab²

Using the following identity

(x – y)³ = x³ – y³ –3×x²×y + 3×y²×x

Modifying the given expression as following

(2a)³ – b³ –3×(2a)²×b + 3×b²×2a

= (2a – b)³

(iii) 27 – 125a³ – 135a + 225a²

Using the following identity

(x – y)³ = x³ – y³ –3×x²×y + 3×y²×x

27 – 125a³ – 135a + 225a²

= 3³ – (5a)³ –3×(3)²×5a + 3×(5a)²×5a

= (3 – 5a)³

(iv) 64a³ – 27b³ – 144a²b + 108b²a

(x – y)³ = x³ – y³ –3×x²×y + 3×y²×x

Modifying the given expression as following

(4a)³ – (3b)³ – 3×(4a)²×3b + 3×(3b)²× 4a

(4a – 3b)³

(x – y)³ = x³ – y³ –3×x²×y + 3×y²×x

Modifying the given expression as following

Q9.Verify

Ans.

Using the  following identity

Using the following identity

Hence Proved

Q10.Factorise each of the following

Ans.

Modifying the given expression according to the identity

Modifying the given expression according to the identity

Q11.Factorise

Using the following identity

Modifying the given expression according to the identity

Q12.Verify that

Applying the following identity

Dividing and multiplying the RHS by 2

Q13.  If x + y + z = 0, show that x3 + y3 + z3 = 3 xyz.
Ans.
Using the following identity

Since, x + y + z = 0
x3 + y3 + z3 – 3 xyz  = 0

x3 + y3 + z3 = 3 xyz
Hence if x + y + z = 0, then  x3 + y3 + z3 = 3 xyz

See the video for Solutions of Question 1 to Question 13

Q14.Without actually calculating the cubes, find the value of each of the following
(i) (– 12)
3 + (7)3 + (5)3
(ii) (28)3 + (– 15)3 + (– 13)3

Ans.
(i) We have, (12)3 + (7)3 + (5)3
Let x = 12, y = 7 and z = 5
Then, x + y + z = 12 + 7 + 5 = 0
We know that if x + y + z = 0, then, x3 + y3 + z3 = 3xyz
∴ (-12)3 + (7)3 + (5)3 = 3×12×7×5
=  1260

(ii) We have, (28)3 + (15)3 + (13)3
Let x = 28, y = 15 and z = 13
Then, x + y + z = 28 – 15 – 13 = 0
We know that if x + y + z = 0, then x3 + y3 + z3 = 3xyz
∴ (28)3 + (15)3 + (13)3 = 3×28×15×13
= 16380

Q15.Give possible expressions for the length and breadth of each of the following rectangles, in which their areas are given
(i) Area 25a2 – 35a + 12
(ii) Area 35y2 + 13y – 12

Ans.
Area of a rectangle = Length x Breadth
(i) 25a2 – 35a + 12 = 25a2 – 20a – 15a + 12

= 5a(5a – 4) – 3(5a – 4) = (5a – 4)(5a – 3)

Thus, the possible length and breadth are (5a – 3) and (5a – 4).

(ii) 35y2+ 13y -12 = 35y2 + 28y – 15y -12
= 7y(5y + 4) – 3(5y + 4) = (5 y + 4)(7y – 3)
Thus, the possible length and breadth are (7y – 3) and (5y + 4).

Q16.What are the possible expressions for the dimensions of the cuboids whose volumes are given below?
(i) Volume 3x2 – 12x
(ii) Volume 12ky2 + 8ky – 20k
Ans.
Volume of a cuboid = Length x Breadth x Height
(i) We have, 3x2 – 12x = 3(x2 – 4x)
= 3 x x x (x – 4)
∴ The possible dimensions of the cuboid are 3, x and (x – 4).

(ii) We have, 12ky2 + 8ky – 20k
= 4[3ky2 + 2ky – 5k] = 4[k(3y2 + 2y – 5)]
= 4 x k x (3y2 + 2y – 5)
= 4k[3y2 – 3y + 5y – 5]
= 4k[3y(y – 1) + 5(y – 1)]
= 4k[(3y + 5) x (y – 1)]
= 4k x (3y + 5) x (y – 1)
Thus, the possible dimensions of the cuboid are 4k, (3y + 5) and (y -1).

## NCERT Solutions of Science and Maths for Class 9,10,11 and 12

### NCERT Solutions for class 9 maths

 Chapter 1- Number System Chapter 9-Areas of parallelogram and triangles Chapter 2-Polynomial Chapter 10-Circles Chapter 3- Coordinate Geometry Chapter 11-Construction Chapter 4- Linear equations in two variables Chapter 12-Heron’s Formula Chapter 5- Introduction to Euclid’s Geometry Chapter 13-Surface Areas and Volumes Chapter 6-Lines and Angles Chapter 14-Statistics Chapter 7-Triangles Chapter 15-Probability Chapter 8- Quadrilateral

### NCERT Solutions for class 9 science

 Chapter 1-Matter in our surroundings Chapter 9- Force and laws of motion Chapter 2-Is matter around us pure? Chapter 10- Gravitation Chapter3- Atoms and Molecules Chapter 11- Work and Energy Chapter 4-Structure of the Atom Chapter 12- Sound Chapter 5-Fundamental unit of life Chapter 13-Why do we fall ill ? Chapter 6- Tissues Chapter 14- Natural Resources Chapter 7- Diversity in living organism Chapter 15-Improvement in food resources Chapter 8- Motion Last years question papers & sample papers

### NCERT Solutions for class 10 maths

 Chapter 1-Real number Chapter 9-Some application of Trigonometry Chapter 2-Polynomial Chapter 10-Circles Chapter 3-Linear equations Chapter 11- Construction Chapter 4- Quadratic equations Chapter 12-Area related to circle Chapter 5-Arithmetic Progression Chapter 13-Surface areas and Volume Chapter 6-Triangle Chapter 14-Statistics Chapter 7- Co-ordinate geometry Chapter 15-Probability Chapter 8-Trigonometry

CBSE Class 10-Question paper of maths 2021 with solutions

CBSE Class 10-Half yearly question paper of maths 2020 with solutions

CBSE Class 10 -Question paper of maths 2020 with solutions

CBSE Class 10-Question paper of maths 2019 with solutions

### NCERT Solutions for Class 10 Science

 Chapter 1- Chemical reactions and equations Chapter 9- Heredity and Evolution Chapter 2- Acid, Base and Salt Chapter 10- Light reflection and refraction Chapter 3- Metals and Non-Metals Chapter 11- Human eye and colorful world Chapter 4- Carbon and its Compounds Chapter 12- Electricity Chapter 5-Periodic classification of elements Chapter 13-Magnetic effect of electric current Chapter 6- Life Process Chapter 14-Sources of Energy Chapter 7-Control and Coordination Chapter 15-Environment Chapter 8- How do organisms reproduce? Chapter 16-Management of Natural Resources

### NCERT Solutions for class 11 maths

 Chapter 1-Sets Chapter 9-Sequences and Series Chapter 2- Relations and functions Chapter 10- Straight Lines Chapter 3- Trigonometry Chapter 11-Conic Sections Chapter 4-Principle of mathematical induction Chapter 12-Introduction to three Dimensional Geometry Chapter 5-Complex numbers Chapter 13- Limits and Derivatives Chapter 6- Linear Inequalities Chapter 14-Mathematical Reasoning Chapter 7- Permutations and Combinations Chapter 15- Statistics Chapter 8- Binomial Theorem Chapter 16- Probability

CBSE Class 11-Question paper of maths 2015

CBSE Class 11 – Second unit test of maths 2021 with solutions

### NCERT solutions for class 12 maths

 Chapter 1-Relations and Functions Chapter 9-Differential Equations Chapter 2-Inverse Trigonometric Functions Chapter 10-Vector Algebra Chapter 3-Matrices Chapter 11 – Three Dimensional Geometry Chapter 4-Determinants Chapter 12-Linear Programming Chapter 5- Continuity and Differentiability Chapter 13-Probability Chapter 6- Application of Derivation CBSE Class 12- Question paper of maths 2021 with solutions Chapter 7- Integrals Chapter 8-Application of Integrals

Class 12 Solutions of Maths Latest Sample Paper Published by CBSE for 2021-22 Term 2

Class 12 Maths Important Questions-Application of Integrals

Class 12 Maths Important questions on Chapter 7 Integral with Solutions for term 2 CBSE Board 2021-22

Solutions of Class 12 Maths Question Paper of Preboard -2 Exam Term-2 CBSE Board 2021-22

Solutions of class 12  maths question paper 2021 preboard exam CBSE Solution

Scroll to Top